Pengaruh Waktu Kontak Terhadap Penyerapan Ion Logam Cr+6 Menggunakan Biomassa Alga Hijau (Mougeotia sp) - Diah Febriani Saputri; Mawardi Anwar (Departemen Kimia FMIPA UNP, 2020)
Chromium(VI) is a dangerous pollutant that the United States Envionmetal Protection Agency (US EPA) has identified as disturbing humans because of its toxicity. Even Cr (VI) is one of the most common pollutants is at number three in waters near industries. For this reason it is necessary to limit and overcome Cr (VI) in the waters. Biosorption is present as an alternative that can remove pollutants in waters by utilizing abundant natural materials. Green alga is one the natural materials used for biosorption. This is because the functional groups that exist on the surface of the cell walls play an important role in binding metals such as amides, amines, hydroxyl, carbonyl and carboxyl. This research was conducted using the Batch method with variations is contact time. The result showed that the optimum condition of contact time was 60 minutes with adsorption of 4,122 mg/ g.The characterization of green algae (Mougeotia sp) using FTIR was carried out to see the functional groups that play a role in adsorption Cr+6.